STRATEGI BAURAN PEMASARAN PADA KATERING GABE DI KOTA MEDAN - Elizon Nainggolan; Heni Vricya Silalahi; Rosdiana Rosdiana (Universitas Negeri Medan, 2022)
Marketing Mix Strategy In Gabe Catering In Medan City. This study aims to determine the marketing mix strategy at the GABE Catering business in Medan City. How are the strategies implemented during the GABE catering business journey in the face of increasingly dynamic business competition, the problems of the covid-19 pandemic, and the corella virus disease in 2019 in Indonesia, especially North Sumatra. The type of research used is qualitative research with a descriptive approach. The number of subjects in this study 1 business owner and 2 customers as data validation. The analysis technique in this study uses observation, interviews, and documentation. The object of this research is the strategy of catering entrepreneurs in developing their business in the marketing mix of GABE Catering in Medan City. The data collection techniques used were observation, interviews and documentation. Based on the results of data analysis, it is found that there are several strategies that are carried out by GABE catering entrepreneurs in the city of Medan in developing their business, namely marketing mix strategies, strategies for building family relationships with employees, and strategies for building family relationships with customers.